Metal organic frameworks as a drug delivery system for flurbiprofen - Al Haydar, Muder; Abid, Hussein Rasool; Sunderland, Bruce; Wang, Shaobin (Dove Medical Press Ltd., 2017)
Background: Metal organic frameworks (MOFs) have attracted more attention in the last decade because of a suitable pore size, large surface area, and high pore volume. Developing biocompatible MOFs such as the MIL family as a drug delivery system is possible. Purpose: Flurbiprofen (FBP), a nonsteroidal anti-inflammatory agent, is practically insoluble in aqueous solution, and, therefore, needs suitable drug delivery systems. Different biocompatible MOFs such as Ca-MOF and Fe-MILs (53, 100, and 101) were synthesized and employ ed for FBP delivery. Patients and methods: A sample of 50 mg of each MOF was mixed and stirred for 24 h with 10 mL of 5 mg FBP in acetonitrile (40%) in a sealed container. The supernatant of the mixture after centrifuging was analyzed by high-performance liquid chromatography to determine the loaded quantity of FBP on the MOF. The overnight-dried solid material after centrifuging the mixture was analyzed for loading percent using X-ray diffraction, Fourier-transform infrared spectroscopy, scanning electron microscopy, nuclear magnetic resonance, and FBP release profile. Results: The loading values of FBP were achieved at 10.0%±1%, 20%±0.8%, 37%±2.3%, and 46%±3.1% on Ca-MOF, Fe-MIL-53, Fe-MIL-101, and Fe-MIL-100, respectively. The FBP release profiles were investigated in a phosphate buffer solution at pH 7.4. The total release of the FBP after 2 days was obtained at 72.9, 75.2, 78.3, and 90.3% for Ca-MOF, Fe-MIL-100, Fe-MIL-53, and Fe-MIL-101, respectively. Conclusion: The MOFs are shown to be a promising drug delivery option for FBP with a significant loading percent and relatively prolonged drug release. © 2017 AL Haydar et al.